Consumer Behavior, Global Edition - Schiffman, Leon G; Wisenblit, Joseph L.; Schiffman, Leon G. (Pearson International Content, 2018)
For undergraduate and graduate courses in consumer behaviour. Consumer Behavior, 12th Edition explores how the examination and application of consumer behaviour is central to the planning, development, and implementation of successful marketing strategies. With an emphasis on developing a variety of useful skills, this text prepares students for careers in brand management, advertising, and consumer research. The 12th Edition has been significantly updated to address contemporary trends and issues, including the role of new media, technological advances, and recent ethical concerns affecting the industry. The full text downloaded to your computer With eBooks you can: search for key concepts, words and phrases make highlights and notes as you study share your notes with friends eBooks are downloaded to your computer and accessible either offline through the Bookshelf (available as a free download), available online and also via the iPad and Android apps. Upon purchase, you'll gain instant access to this eBook. Time limit The eBooks products do not have an expiry date. You will continue to access your digital ebook products whilst you have your Bookshelf installed.